Positive Parental Treatment and its Relationship with the Psychological Health of Children with Physical Disabilities in Amman Governorate from the Point of view of their Parents - Al Momani, Randa Mousa; Al Majali, Areen Bajes A.Q (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to identify the relationship between positive parental treatments with the psychological health of children with physical disabilities in the Amman governorate from the point of view of their parents. Methods: The study employed a descriptive-correlative approach with two questionnaires: one on positive parental treatment (20 statements) and another on psychological health (14 statements), each validated for reliability. Participants were parents of children with physical disabilities from four Amman centres. A random sample of (150) guardians was chosen from a pool of (250) eligible guardians. Results were categorized into high (3.68-5), moderate (2.34-3.67), and low (1-2.33) degrees. Results: The results of the study showed that the degree of positive parental treatment of children with physical disabilities in the Governorate, Amman, from the point of view of their parents, was high with a mean of (3.86), and the degree of their psychological health was moderate with a mean of (3.42). The results indicate a statistically significant positive correlation between the degree of positive parenting and the level of psychological well-being of children with physical disabilities in the capital city of Amman. Conclusions: The study suggests boosting children's morale with motor disabilities through motivational support, embracing mistakes, and providing consistent guidance. It emphasizes the importance of parents fostering an acceptance of the disability, encouraging activities that empower the child to believe they can accomplish various tasks despite their limitations.